2013
DOI: 10.1002/pssb.201350034
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport through perylene bisimide molecular junctions: An electrochemical approach

Abstract: Single molecular junction conductances of a family of five symmetric and two unsymmetric perylene tetracarboxylic bisimides (PBI) with variable bay‐area substituents were studied employing a scanning tunneling microscope (STM)‐based break junction technique. The stretching experiments provide clear evidence for the formation of single molecular junctions and π–π stacked dimers. Electrolyte gating demonstrates a distinct gating effect in symmetric molecular junctions, which strongly depends on molecular structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Electrochemical gating allows precise and reproducible control of very strong gating fields in the molecular junction and switching of molecular wires between different chemical redox states. Examples of electrochemical gating of wired single-molecule bridges with the following redox centers include viologens (29,(108)(109)(110), pyrrolo-tetrathiafulvalene (pTTF) (107,111), catechol-type dithiol-terminated OPEs (112), perylene tetracarboxylic bisimides (113)(114)(115)(116), oligoanilines (117,118), anthraquinone (119,120), and benzodifuran (63). Figure 13 provides an example of the electrochemical gating of a pTTF molecular bridge.…”
Section: Switching or Gating Single-molecule Conductancementioning
confidence: 99%
“…Electrochemical gating allows precise and reproducible control of very strong gating fields in the molecular junction and switching of molecular wires between different chemical redox states. Examples of electrochemical gating of wired single-molecule bridges with the following redox centers include viologens (29,(108)(109)(110), pyrrolo-tetrathiafulvalene (pTTF) (107,111), catechol-type dithiol-terminated OPEs (112), perylene tetracarboxylic bisimides (113)(114)(115)(116), oligoanilines (117,118), anthraquinone (119,120), and benzodifuran (63). Figure 13 provides an example of the electrochemical gating of a pTTF molecular bridge.…”
Section: Switching or Gating Single-molecule Conductancementioning
confidence: 99%
“…In Ref. 60 it was found experimentally that increasing the gate voltage in one direction leads to a rapid increase in the conducance while a voltage with the opposite sign had no effect. This was interpreted as a reduction of the complex with a negative potential but in terms of our Figure 2 it can also be seen as a climbing up of the peak related to the HOMO in both transport regimes.…”
Section: Application Of An Electrochemical Gate Potentialmentioning
confidence: 99%
“…We studied the change in their conductance in response to the binding of three analytes, namely TNT, BEDT-TTF and TCNE, and found that the five different responses provided a unique fingerprint for the discriminating sensing of each analyte. This ability to sense and discriminate was a direct consequence of the extended π system of the PBI backbone, which strongly binds the analytes, combined with the different charge distribution of the five PBI derivatives, which leads to a unique electrical response to analyte binding.Recently, it has been experimentally demonstrated that single PBI-based molecules can be attached to gold electrodes and their electrical conductance can bemeasured [29]. In the present paper our aim is to demonstrate that the extended π systems of PBIs make them ideal candidates for the single-molecule, label-free sensing of a variety of analytes.…”
mentioning
confidence: 92%
“…Four molecules (Py-PBI, P-PBI, Cl-PBI, S-PBI) possess pyridyl anchor groups at opposite ends and are therefore symmetric. The fifth molecule (aPy-PBI) has a pyridyl anchor group on the top and a cyclohexyl anchor group on the bottom [29] and is asymmetric.…”
mentioning
confidence: 99%
See 1 more Smart Citation